1991
DOI: 10.1111/j.1365-2222.1991.tb01662.x
|View full text |Cite
|
Sign up to set email alerts
|

Group V allergens in grass pollens. II. Investigation of group V allergens in pollens from 10 grasses

Abstract: In an earlier study an allergen from Phleum pratense (timothy) pollen, Phl p V, has been isolated and physicochemically characterized. In this study Phl p V and immunochemically similar components from other grass pollens (group V allergens) have been investigated using immunoelectrophoretic techniques. To study the allergenic importance of the group V allergens, the allergenic compositions of 10 grass pollen extracts were investigated in crossed radioimmunoelectrophoresis (CRIE) using 20 sera from grass polle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
66
0
1

Year Published

1995
1995
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 29 publications
(27 reference statements)
3
66
0
1
Order By: Relevance
“…Pollen allergens from groups 1 and 5 are highly conserved in most clinically relevant grasses (33)(34)(35)(36) and proved to be important in this study. However, the 28-30-and 32-35-kDa components likely related to allergens from groups 5 and 1, respectively, showed more than 50% inhibition with the Lp and GII extracts, and less than 50% inhibition when the GI extract was used.…”
Section: Discussionmentioning
confidence: 72%
“…Pollen allergens from groups 1 and 5 are highly conserved in most clinically relevant grasses (33)(34)(35)(36) and proved to be important in this study. However, the 28-30-and 32-35-kDa components likely related to allergens from groups 5 and 1, respectively, showed more than 50% inhibition with the Lp and GII extracts, and less than 50% inhibition when the GI extract was used.…”
Section: Discussionmentioning
confidence: 72%
“…Several group 5 molecules have already been purified and/or cloned [6, 7, 8, 9, 10, 11, 12, 13, 14]and are described as a group of nonglycosylated, highly homologous proteins with an apparent molecular mass (M r ) on SDS-PAGE of 25–33 kDa [15, 16, 17]. By immunoblot analysis, group 5 allergens were shown to migrate as a doublet around this M r , and both bands showed IgE-binding capacities [4, 5, 18]. Matthiesen and Lowenstein [4]were the first to designate this doublet of natural Phl p 5 as the a-form and b-form with an approximate M r of 32 and 29 kDa, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…To date, grass pollen allergens are divided into 11 groups [1, 2, 3, 4, 5], of which group 1 and group 5 have been identified as the most important. Several group 5 molecules have already been purified and/or cloned [6, 7, 8, 9, 10, 11, 12, 13, 14]and are described as a group of nonglycosylated, highly homologous proteins with an apparent molecular mass (M r ) on SDS-PAGE of 25–33 kDa [15, 16, 17].…”
Section: Introductionmentioning
confidence: 99%
“…Its relationship to this group of major allergens was defined by immunological reactivities with Mabs and by Nterminal microsequencing [5,15]. By comparing cDNA sequences of a number of group V clones it was confirmed that the heterogeneity is caused by genetic variations, a feature possibly reflecting the character of gene families.…”
Section: Discussionmentioning
confidence: 92%
“…The potency of these allergens is related to the fact that they can be released into the environment from the pollen with the starch granules and thus are small enough to enter the human airway to induce an IgE-mediated response in asthmatic patients [4]. These allergens represent a highly variable group of proteins which can be distinguished in timothy grass pollen by molecular weight into group Va = 38 kDa (more basic proteins) and group Vb = 32 kDa (more acidic proteins) [5,6]. Cloning and sequencing of group Va cDNAs revealed a homology of more than 85% among these allergens [7-91 indicating that they are isoforms of a gene family in related grasses.…”
Section: Introductionmentioning
confidence: 99%